Association between inflammatory score, healthy lifestyle, and cardiovascular disease: a national cohort study - Zhao, Han-Qing; Lv, Jia-Le; Gao, Yuan-Zhi; Hu, Bo; Du, Zong-Da; Wang, Yan; Wang, Mei-Lin; Hou, Meng-Di; Li, Fang; Xing, Xue; Sun, Ming-Hui (Frontiers in Nutrition, 2025)
BackgroundThe inflammation score is currently regarded as a reliable composite index for comprehensive assessment of inflammatory status. However, the relationship between inflammation score and cardiovascular disease (CVD) is unclear. Thus, we aimed to explore the association of inflammatory score with CVD, as well as to evaluate whether adhering to a healthy lifestyle could alleviate this association.MethodsWe analyzed 6,164 participants aged ≥45 years who entered a prospective cohort study of the China Longitudinal Study of Health and Retirement (CHARLS) between 2011 and 2012 and were followed up for CVD incidence untill 2018. The inflammatory score was measured by summing of the Z-scores for C-reactive protein and white blood cell count at baseline. The healthy lifestyle score was calculated by four factors, smoking status, alcohol consumption, body mass index, and sleep duration. Cox proportional hazard models were utilized to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) for the incidence of CVD.ResultsDuring the 7-year follow-up period, there were 761 incident cases of CVD. Compared with the lowest tertiles, the highest inflammatory score was associated with an elevated risk of CVD (HR = 1.25, 95% CI = 1.04–1.49). Compared to the unhealthy lifestyle, participants adhered to a healthy lifestyle was inversely associated with CVD risk (HR = 0.74, 95% CI = 0.60–0.93). Of note, when participants adhered to a healthy lifestyle, the higher inflammatory score was no longer significantly correlated with CVD risk (HR = 1.00, 95% CI = 0.76–1.34). Additionally, a multiplicative interaction was detected between inflammatory score and healthy lifestyle score for CVD risk (p interaction <0.05).ConclusionThe inflammation score was associated with higher risk of CVD incidence, but adherence to a healthy lifestyle may mitigate the adverse association of inflammation score and CVD among the middle-aged and older participants.